Estudo experimental da microrretificação de canais em Quartzo-α - Monteiro, Mateus Oliveira (Universidade Federal de São Carlos, 2025)
Single crystals, such as quartz (SiO₂), exhibit attractive mechanical properties, including a regular atomic arrangement, dimensional stability at high temperatures, and low mass, making them relevant in applications such as sensors and electronic resonators. This study focuses on the microgrinding of α-quartz on the AT-cut plane, aiming to evaluate the feasibility of applying this process to hard and brittle materials, in comparison to the abrasive disc process. A microgrinding tool with a 1.2 mm diameter and abrasive grit with an average equivalent diameter of 30 μm was used to analyze the effect of varying machining parameters — depth of cut, feed per revolution, and tool rotation — on the quality of the machined surface. The volume removed per revolution (VRR), based on the abrasive disc work by Araújo (2015), served as a reference to ensure technological comparability between processes by assessing the average size of surface defects. A total of 18 experiments were conducted using KG Sorensen FG 1093FF microgrinding tools under different conditions, aiming to evaluate the formation of critical damage (chipping) through optical microscopy, in addition to investigating the potential influence of pocket clogging in the tool, which affects the quartz removal mechanism. The results indicated that although the microgrinding tool is more sensitive to variations in VRR, with a sharper increase in surface defects, it offers significant advantages in precision machining contexts. Its geometry allows for complex shape machining, overcoming the limitations of abrasive disc cutting. The microgrinding tool proved particularly effective at a cutting depth of 0.1 mm and feed rates of 0.0001290; 0.000042; and 0.000025 mm/rev, where no significant impact on the removal mechanism or cutting performance was observed. It is concluded that, despite challenges such as pronounced tool wear and material accumulation in the tool pockets, the microgrinding process holds potential for the manufacturing of miniaturized components and is promising for applications where precision and geometric complexity are essential.
Experimental investigation of micro-grinding processes for channel fabrication in α-Quartz
Keywords: Quartzo; Microrretificação; Retificação; Abrasivo; Monocristal; Micro grinding; Grinding; Abrasive; Single crystal; ENGENHARIAS::ENGENHARIA MECANICA::PROCESSOS DE FABRICACAO